Knowledge and Adaptation Practices: Baseline Data for the Development of Climate Change Engagement Model - Corpuz, Alma M. (Future Science / FSH-PH Publications, 2023)
Climate change (CC) will continue to harm the environment if mitigation efforts are slow. Raising the CC knowledge and awareness of individuals is crucial in prompting significant mitigating action or adaptation practices. In addition, empowering young people will potentially ignite more innovative strategies that are helpful in decelerating the impacts of CC. The study aimed to determine students’ knowledge of CC and their adaptive practices. Based on the findings, a model to engage students in CC action was developed. The respondents were 132 students in a State University in Region III enrolled in AY 2022-2023. Data were gathered using a validated self-made questionnaire. Findings revealed that while most respondents were knowledgeable of the concept of climate change (62.88%), a sizable percentage were still misinformed. In addition, the respondents knew the causes of CC such as the emission of greenhouse gases (87.12%), deforestation (57.58%), and excessive fertilizer use (37.88%) but some causes of climate change were unknown to them. Moreover, most of them were cognizant of the consequences of climate change which include excessive rain (96.21%), flood (95.45%), and melting of snow (94.70%). But the response to “drought” as one of the consequences of climate change was only known to a few students (47.73%). As to the knowledge of the health effects of climate change, most students knew CC raises respiratory, water-borne, and skin diseases but some expressed their lack of knowledge about other diseases such as the possibility of triggering cancer and mental health issues. Moreover, students have developed CC adaptive practices such as consuming more fruits and vegetables than meat and conserving energy use at home, but they were observed to be inconsistent in some areas such as in practicing the 3Rs and in throwing away less food. The F-value of 0.021 and 0.82 p-value, to compare the CC adaptive practices of the respondents with respect to gender, support the acceptance of the null hypothesis. Gender is not a determinant of CC adaptive practices. This indicates that gender is not a barrier to CC action. The study concludes that students have limited knowledge about climate change, especially on the health impacts. Also, the students’ CC adaptive practices imply lack of commitment to act on CC. The study recommends strengthening the integration of climate change into school policies, research, extension, and instruction and a strong support of school stakeholders in their implementation. A climate change engagement model is an output of this study which may be considered by schools in prompting students to participate in CC action. A future study may include the factors that hinder students’ consistent involvement in CC action despite their awareness and knowledge about the negative consequences.